Identification and Antifungal Mechanism of a Novel Actinobacterium Streptomyces huiliensis sp. nov. Against Fusarium oxysporum f. sp. cubense Tropical Race 4 of Banana - Qi, Dengfeng; Zou, Liangping; Zhou, Dengbo; Zhang, Miaoyi; Wei, Yongzan; Zhang, Lu; Xie, Jianghui; Wang, Wei (Frontiers in Microbiology, 2021)
Banana is an important fruit crop. Fusarium wilt caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) seriously threatens the global banana industry. It is difficult to control the disease spread using chemical measures. In addition, commercial resistant cultivars are also lacking. Biological control is considered as a promising strategy using antagonistic microbes. Actinomycetes, especially Streptomyces, are potential sources of producing novel bioactive secondary metabolites. Here, strain SCA2-4T with strong antifungal activity against Foc TR4 was isolated from the rhizospheric soil of Opuntia stricta in a dry hot valley. The morphological, physiological and chemotaxonomic characteristics of the strain were consistent with the genus Streptomyces. Based on the homology alignment and phylogenetic trees of 16S rRNA gene, the taxonomic status of strain SCA2-4T exhibited a paradoxical result and low bootstrap value using different algorithms in the MEGA software. It prompted us to further discriminate this strain from the closely related species by the multilocus sequence analysis (MLSA) using five house-keeping gene alleles (atpD, gyrB, recA, rpoB and trpB). The MLSA trees calculated by three algorithms demonstrated that strain SCA2-4T formed a distinct clade with Streptomyces mobaraensis NBRC 13819T. The MLSA distance was above 0.007 of the species cut-off. Average nucleotide identity (ANI) values between strain SCA2-4T genome and two standard strain genomes were below 95-96% of the novel species threshold. Strain SCA2-4T was assigned to a novel species of the genus Streptomyces and named as Streptomyces huiliensis sp. nov. The sequenced complete genome of SCA2-4T encoded 51 putative biosynthetic gene clusters of secondary metabolites. Genome alignment revealed that ten gene clusters were involved in the biosynthesis of antimicrobial metabolites. It was supported that strain SCA2-4T showed strong antifungal activities against the pathogens of banana fungal diseases. Extracts from the culture filtrate of strain SCA2-4T seriously destroyed cell structure of Foc TR4 and inhibited mycelial growth and spore germination. These results implied that strain SCA2-4T could be a promising candidate for biological control of banana Fusarium wilt.